Herbicide detection in groundwater in Córrego Rico-SP watershed - Santos, E. A.; Correia, N. M.; Silva, José Roberto Marques [UNESP]; Velini, Edivaldo Domingues [UNESP]; Passos, A. B. R. J.; Durigan, Julio Cezar [UNESP] (Univ Federal Vicosa, 2015)
Due to the large amount of pesticides applied in agriculture, mainly herbicides, there is a growing concern about a possible environmental contamination with these products, including water bodies. Given the above, the aim of the present work was to detect and quantify herbicides through multiresidue analysis in water samples collected in semi-artesian wells and springs in a rural area of the city of Jaboticabal (SP). Samples were collected from 32 wells and 13 water springs, in three different seasons: October 2010, February 2011 and May 2011. Additionally, samples at a residence in the urban area were also collected. Analysis using high performance liquid chromatography coupled to mass spectrometry was performed and herbicides ametryn, amicarbazone, clomazone, diclosulan, diuron, hexazinone, imazapic, imazapyr, isoxaflutole, S-metolachlor, sulfentrazone, sulfometuron-methyl, and tebuthiuron were evaluated. In semi-artesian wells, an incresed quantity of herbicides was found in comparison with the water springs. Among the tested herbicides, hexazinone, imazapyr and sulfentrazone were detected in measurable amounts in accordance with the analytical method applied, while clomazone was the most common herbicide being detected in more than 60% of the samples. Ametryn, diuron and amicarbazone herbicides were also detected. Diclosulan, imazapic, isoxaflutole, S-metolachlor, sulfometuron-methyl, and tebuthiuron were not detected in any sample. Inappropriate use of these products without prior knowledge of the behavior of the soil can lead to groundwaters and water springs contamination, thus an ongoing monitoring of this resource becomes very important.

Em vista da grande quantidade de agroquímicos aplicados na agricultura, principalmente os herbicidas, cresce a preocupação com a possível contaminação do ambiente com esses produtos, inclusive em corpos dâ€(tm)água. Diante do exposto, o objetivo deste trabalho foi detectar e quantificar herbicidas, por meio de análise multirresíduo, em amostras de água coletadas em poços semiartesianos e nascentes, em uma área rural da cidade de Jaboticabal (SP). Foram coletadas amostras em 32 poços e 13 nascentes, em três épocas: outubro de 2010, fevereiro e maio de 2011. Foram coletadas, adicionalmente, amostras em uma residência na área urbana. Foi realizada análise por cromatografia líquida de alta eficiência acoplada à espectrometria de massas e foram avaliados os herbicidas ametryn, amicarbazone, clomazone, diclosulan, diuron, hexazinone, imazapic, imazapyr, isoxaflutole, S-metolachlor, sulfentrazone, sulfometuron-methyl e tebuthiuron. Em poços semiartesianos foram encontrados mais herbicidas em relação às nascentes. Entre os herbicidas avaliados, hexazinone, imazapyr e sulfentrazone foram detectados em valores quantificáveis de acordo com o método analítico, ao passo que o clomazone foi o herbicida mais frequente, sendo detectado em mais de 60% das amostras. Foram detectados também os herbicidas ametryn, amicarbazone e diuron. Em nenhuma das amostras foram detectados os herbicidas diclosulan, imazapic, isoxaflutole, S-metolachlor, sulfometuron-methyl e tebuthiuron. A utilização incorreta desses produtos, sem um prévio conhecimento do comportamento deles no solo, faz com que haja contaminação de águas subterrâneas e nascentes, tornando importante o monitoramento constante desse recurso.
Detecção de herbicidas em água subterrânea na microbacia do Córrego Rico-SP
Keywords: Sugarcane; LC-MS/MS; Water springs; Semi-artesian wells; Cana-de-açúcar; LC-MS/MS; |Nascentes; Poços semiartesianos